2020
DOI: 10.1186/s12955-020-01456-3
|View full text |Cite
|
Sign up to set email alerts
|

Health, subjective financial situation and well-being: a longitudinal observational study

Abstract: Background: An individual's financial situation is a key contributor to their overall well-being. Existing research has examined the direct economic consequences of changes in health upon out-of-pocket healthcare expenditure, participation in the labour force and potential earnings. There is also research exploring an individual's concern about their subjective financial situation regardless of the level of their income or work status on their health. In contrast, this paper conducts a causal analysis of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 43 publications
2
20
0
Order By: Relevance
“…Our results showed that the perception of financial difficulties (item of the SQoL-MHA “financial trade-offs”) was significantly and inversely associated with the domain scales “relationship” and “hope”. This is consistent with literature as evidence shows that subjective feelings of financial hardship are associated with shame, self-stigma and hopelessness ( 48 50 ). In addition, subjective financial hardship tends to be more associated with mental health problems than objective financial hardship, emphasizing the importance of the assessment of subjective financial difficulties ( 48 ).…”
Section: Discussionsupporting
confidence: 92%
“…Our results showed that the perception of financial difficulties (item of the SQoL-MHA “financial trade-offs”) was significantly and inversely associated with the domain scales “relationship” and “hope”. This is consistent with literature as evidence shows that subjective feelings of financial hardship are associated with shame, self-stigma and hopelessness ( 48 50 ). In addition, subjective financial hardship tends to be more associated with mental health problems than objective financial hardship, emphasizing the importance of the assessment of subjective financial difficulties ( 48 ).…”
Section: Discussionsupporting
confidence: 92%
“…There is an increasing evidence base that both objective and subjective financial circumstances is a key contributor to individual overall well-being throughout their lifecourse (Downward et al, 2020;Marshall et al, 2020). However, access to the appropriate longitudinal data to test this relationship, particularly data on childhood circumstances, has been limited to date.…”
Section: Predicator: Financial Circumstances In Childhood and Adulthoodmentioning
confidence: 99%
“…Evidence on the important role childhood material circumstances on various physical and mental health outcomes in adulthood has increased considerably over the last two decades (Carr, 2019;Morrissey & Kinderman, 2020). However, despite research indicating that both objective and subjective financial circumstances are key contributors to individual overall wellbeing in adulthood (Stafford et al, 2015;Wood et al, 2017;Downward et al, 2020;Marshall et al,, 2020), the relationship between childhood circumstances and adult mental wellbeing remains far less developed (Carr, 2019). Conceptually, an increased understanding of the impact of material circumstances in childhood on adult mental wellbeing outcomes is important for two interlinked reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Research has primarily provided evidence on the association between (access to) health and objective economic inequality. In conjunction with the objective financial situation, there is, however, also a positive correlation between subjective financial well-being and (mental) health outcomes [34]. Also, a language barrier or a significant degree of illiteracy affects a person's ability to access and use the necessary health care services [35,36].…”
Section: Socio-economic Determinants At the Client Level And The Care Contextmentioning
confidence: 99%